Respuesta :

Answer:

D. [tex] x = 3 \pm \sqrt{10} [/tex]

Step-by-step explanation:

[tex] x^2 - 6x - 1 = 0 [/tex]

[tex] x = \dfrac{-b \pm \sqrt{b^2 - 4ac}}{2a} [/tex]

a = 1; b = -6; c = -1

[tex] x = \dfrac{-(-6) \pm \sqrt{(-6)^2 - 4(1)(-1)}}{2(1)} [/tex]

[tex] x = \dfrac{6 \pm \sqrt{36 + 4}}{2} [/tex]

[tex] x = \dfrac{6 \pm \sqrt{40}}{2} [/tex]

[tex] x = \dfrac{6 \pm \sqrt{4 \times 10}}{2} [/tex]

[tex] x = \dfrac{6 \pm 2 \sqrt{10}}{2} [/tex]

[tex] x = 3 \pm \sqrt{10} [/tex]

ACCESS MORE